2016
DOI: 10.1021/acs.nanolett.6b01593
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Hysteresis for Probing Dzyaloshinskii–Moriya Interaction

Abstract: The interfacial Dzyaloshinskii-Moriya interaction (DMI) is intimately related to the prospect of superior domain-wall dynamics and the formation of magnetic skyrmions. Although some experimental efforts have been recently proposed to quantify these interactions and the underlying physics, it is still far from trivial to address the interfacial DMI. Inspired by the reported tilt of the magnetization of the side edge of a thin film structure, we here present a quasi-static, straightforward measurement tool. By u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 53 publications
4
74
1
1
Order By: Relevance
“…Large effective DMI strenghts have been observed for Pt/Co/Ir stacks 24, 28 . In contrast to symmetric stacks where the interfacial DMI of both interfaces (partially) cancel each other, this system could have an enhanced total DMI, because opposite signs of the DMI are expected for Pt/Co and Ir/Co interfaces 23, 29, 30 (though recently conflicting observations were reported 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large effective DMI strenghts have been observed for Pt/Co/Ir stacks 24, 28 . In contrast to symmetric stacks where the interfacial DMI of both interfaces (partially) cancel each other, this system could have an enhanced total DMI, because opposite signs of the DMI are expected for Pt/Co and Ir/Co interfaces 23, 29, 30 (though recently conflicting observations were reported 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because these new stacks are structurally less symmetrical than the Pt/Co/Pt sample that was used up to now, the DMI (and therefore the success rate of the racetrack) is expected to be increased. The DMI was not measured independently for the samples used in this work, but studies of similar samples, grown in the same lab, can be found in literature 17, 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the DMI constant is measured by the following techniques: by observing the frequency nonreciprocity of spin-wave propagation with Brillouin light spectroscopy [20,42,43], by asymmetric magnetic domain growth, [44] by field-driven domain-wall motion in the creep regime, [43] by current-driven domain-wall motion under applied magnetic field, [45] and by asymmetric hysteresis [46]. Our theory offers another method to obtain the interfacial DMI constant from the direct measurements of the tilt angle of the Dzyaloshinskii domain wall.…”
Section: Discussionmentioning
confidence: 99%
“…Interfacial effects are generally expected to scale as 1/t. In some other studies that have investigated the dependence of D on magnetic layer thickness it has been possible to fit a straight line of the form D ∝ 1/t to DM energy data for thin-film systems [25,26]. Other studies show a linear dependence but with a nonzero intercept, suggesting some contribution from atoms that do not lie at a sharp heavy-metal/ferromagnet interface layer [27].…”
Section: B Dzyaloshinskii-moriya Energymentioning
confidence: 99%